Faktor-faktor yang berhubungan dengan tindakan tidak aman (unsafe action) pada pekerja bagian proses produksi - Erika Vernanda Br Lbn Toruan; Budi Aswin; Kasyani Kasyani; Rd. Halim (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Occupational accidents remain a serious problem in the industrial sector, particularly in the rubber processing industry, which is characterized by high-risk production processes. Most accidents are caused by unsafe actions performed by workers. Purpose: To analyze the factors associated with unsafe actions among workers in the production process unit. Method: This study employed a quantitative approach with a cross-sectional design. The research was conducted among production process workers at PT X Jambi in 2025. A total of 53 workers were selected using a quota sampling technique. Data were collected through questionnaires and observation, then analyzed using univariate and bivariate analysis with the Chi-Square test. Results: This study found that approximately 39.6% of workers engaged in unsafe acts. This study found a significant relationship between knowledge (with a p-value of 0.000), the use of personal protective equipment (p-value of 0.002), and occupational safety and health (K3) supervision (p-value of 0.020) with these unsafe behaviors among workers. Furthermore, length of service (p-value of 1.000) and K3 training (p-value of 1.000) did not show a significant relationship with unsafe acts among workers in the production process. Conclusion: There is a relationship between knowledge, use of PPE, and supervision with unsafe actions among workers. Meanwhile, there is no relationship between work period and training. Keywords: Occupational Accidents; Occupational Safety And Health; Unsafe Action. Pendahuluan: Kecelakaan kerja masih menjadi masalah serius di sektor industri, terutama pada industri pengolahan karet yang berisiko tinggi. Mayoritas kecelakaan kerja terjadi tindakan tidak aman (unsafe action) yang dilakukan pekerja. Tujuan: Untuk menganalisis faktor-faktor yang berhubungan dengan tindakan tidak aman (unsafe action) pada pekerja bagian proses produksi. Metode: Penelitian kuantitatif dengan desain cross-sectional. Sampel penelitian sebanyak 53 pekerja yang dipilih lewat teknik quota sampling. Data diperoleh dari kuesioner dan pengamatan langsung, lalu diolah dengan analisis univariat dan bivariat menggunakan uji Chi-Square. Hasil: Menunjukkan bahwa sekitar 39.6% pekerja ternyata melakukan tindakan yang tidak aman. Penelitian ini menemukan adanya hubungan signifikan antara pengetahuan (dengan nilai p=0.000), pemakaian alat pelindung diri (p=0.002), serta pengawasan keselamatan dan kesehatan kerja atau K3 (p=0,020) dengan perilaku tidak aman tersebut pada pekerja. Selain itu, masa kerja (p=1.000) dan pelatihan K3 (p=1.000) tidak menunjukkan hubungan yang signifikan dengan tindakan tidak aman di kalangan pekerja bagian proses produksi. Simpulan: Terdapat hubungan antara pengetahuan, penggunaan apd, dan pengawasan dengan unsafe action pada pekerja. Sedangkan untuk masa kerja dan pelatihan tidak tidak terdapat memiliki hubungan. Kata Kunci: Kecelakaan Kerja; Keselamatan dan Kesehatan Kerja; Tindakan Tidak Aman.